Valsts pārvalde un tās pakalpojumi - Prūse, Ilze (Latvijas Universitāte, 2007)
Tēmas aktualitāte saistīta ar valsts pārvaldes modernizāciju un e-pārvaldes t.sk. e-pakalpojumu ieviešanu. Lai izveidotu e-pakalpojumu, būtiski ir izprast pakalpojumu jēdzienu publiskajā pārvaldē, lai tā sniegšanu uzlabotu, izmantojot informācijas tehnoloģijas. Taču jautājums par pakalpojumu publiskajā pārvaldē ir daudz dziļāks nekā tikai konkrētas funkcijas optimizācija. Pakalpojumu jēdzienu publiskajā pārvaldē sāk izmantot kā atbildi sabiedrības spiedienam padarīt pārvaldi efektīvāku, ar to saprotot gan tās darbības skaitlisko rādītāju uzlabošanos, gan ērtību radīšanu indivīdiem, kuri vienlaikus ir valsts pārvaldes klienti. Pakalpojumus valsts pārvaldē var definēt dažādi atkarībā no izvirzītajiem uzdevumiem un pakalpojuma saņēmēja individualizācijas pakāpes. Dažādu autoru publikācijās un arī politikas plānošanas dokumentos nav dota viennozīmīga publiskā pakalpojuma definīcija, un funkciju loks, ko šis termins aptver, var būt visai daudzveidīgs, tāpēc katrā konkrētā dokumentā jāpievērš uzmanība pakalpojumu jēdziena apjomam, kas var svārstīties plašās robežās. Lai pētītu pakalpojuma jēdziena izpratni Latvijā, darba pētnieciskajā daļā analizēti Latvijas un Eiropas Savienības politikas plānošanas dokumenti, kā arī tiesību akti, kuri tiešā veidā ietekmē pakalpojuma jēdziena izpratni Latvijas publiskajā pārvaldē. Darba sākumā izvirzītā hipotēze par to, ka publiskās pārvaldes pakalpojumi ir veids, kā pierādīt sabiedrībai publiskās pārvaldes lietderīgumu un darba efektivitāti un, līdz ar to vairot sabiedrības uzticēšanos gan izpildu, gan lēmējvarai tiek apstiprināta daļēji, jo pakalpojumu definēšana pati par sevi iedzīvotāju viedokli par publisko pārvaldi neuzlabos. Tomēr – pakalpojums ir iestādes funkcijas rezultāts un ja tas ir definēts, tad to ir parādīt sabiedrībai un to var izmantot par kritēriju dažādu reformu efektivitātes mērīšanai. Latvijas prakses analīze pierāda, ka e-pārvaldes efektīva ieviešana nav iespējama bez pašas pārvaldes. E-pakalpojumi, bez paša publiskās pārvaldes pakalpojuma arī ir problemātiski, jo informācijas tehnoloģijas nodrošina piegādes kanālu, nevis pašas sniedz pakalpojumu. Kanāls viens pats bez pakalpojuma nekādus uzlabojumus ne pārvaldei, ne klientam nedos.

The importance of this topic in the latest years is concerned with implementation of e-governance solutions in the public administration, including also development of e-services. In order to develop e-service it is necessary to understand meaning of service in the public administration. The main question about substance and role of the service in public administration is much complicated as it looks from the viewpoint of the e-governance. The hypothesis advanced for the study is to define public service as a way to explain society what administration does and to demonstrate effectiveness of the reforms and results of the improvements in the public administration. The concept of public service in the public administration started to develop mainly since last two decades of the 20th century as reply of politicians and administration to the demand coming from society for the more effective governance. Effective governance in this case means request for measurable results and orientation to the market principles. Because in global level improvements in the public administration in the latest years is concerned with implementation of information and communication technologies, also e-governance and e-services are discussed in this study. The main base of empiric part of the study includes analysis of the policy documents and normative acts of European Union and Republic of Latvia. In the level of European Union e-governance and e-services in general are concerned with implementation of Lisbon strategy end following with e-Europe 2002, e-Europe 2005 and 2010 initiatives. Those initiatives and following programmes became the reason for the development of e-services in the national countries. And here concepts of public administration met e-governance. Especially it is important for the countries following Roman or continental system of law. It is necessary to have clear link between public function and public service as a way for implementation of this function. Analysis provided in this study shows wide borders of usage of the service concept in the public administration. The service and the client in the public administration are not the same as in the private relationships. Difference of those approaches and possibility to define borders of the service concept in the public administration are discussed in this study. Service concept can include marketing measure, quantitative measurement of the effectiveness and efficiency in the public administration and execution of the public functions. In the context of the administrative reform and formation of the Informative society in Latvia it should be mentioned importance of the legal concepts. Some unclear definitions in the law On State Governance rises unclear understanding of the service concept in public administration and later difficulties to define public services were met. The hypothesis for the public service as a way to explain society mission of the public administration corroborated partially, because there is no straight relation between satisfaction of society and improvement of public services, but service as unit for further measurements and defined process can become an argument. As regards link between public services and e-government, especially for the countries following continental system of law, it is impossible to develop e-service without the main service what is the result of execution of public function. Wide boarders of the public service concept makes necessary to define it in each policy regarding this concept separately, to have clear understanding of the subject.
Public Governance and It’s Services
Keywords: Politikas zinātne (politoloģija)